2002
DOI: 10.1034/j.1600-6143.2002.020115.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Access to Transplantation for Blood Group B Cadaveric Waiting List Candidates by Using A2 Kidneys: Time for a New National System?

Abstract: Since blood group B end-stage renal disease (ESRD) patients have less access to donor kidneys and a higher minority composition than any other blood group, the United Network for Organ Sharing (UNOS) approved a voluntary national kidney allocation variance to allow organ procurement organizations (OPOs) to preferentially allocate A2 and A2B kidneys to B candidates. The Midwest Transplant Network OPO has preferentially allocated and transplanted kidneys from blood group A2 and A2B donors to our blood group B wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…Similarly, transplant candidates with blood group types B and O wait approximately twice as long as individuals with blood group A and four times as long as people with blood group AB [6]. Since most African Americans with ESRD have blood types B or O, this might further decrease their access to donor kidneys [43,53]. In 2002, the UNOS (United Network of Organ Sharing) implemented the elimination of the priority of HLA-B locus matching from kidney allocation, in order to promote equity in organ allocation by increasing the likelihood of deceased donor transplantation in minority patients [54].…”
Section: Referral For Evaluation Waitlisting and Transplantationmentioning
confidence: 98%
“…Similarly, transplant candidates with blood group types B and O wait approximately twice as long as individuals with blood group A and four times as long as people with blood group AB [6]. Since most African Americans with ESRD have blood types B or O, this might further decrease their access to donor kidneys [43,53]. In 2002, the UNOS (United Network of Organ Sharing) implemented the elimination of the priority of HLA-B locus matching from kidney allocation, in order to promote equity in organ allocation by increasing the likelihood of deceased donor transplantation in minority patients [54].…”
Section: Referral For Evaluation Waitlisting and Transplantationmentioning
confidence: 98%
“…Increased use of blood group A2 and A2B kidneys in blood group B registrants could potentially reduce waiting times for blood group B registrants (4). The median time to transplant for registrants with a previous organ transplant is nearly twice as long as that for registrants waiting for a first transplant, likely reflecting sensitization and the presence of comorbidities.…”
Section: Kidney and Pancreas Transplantation 1995-2004mentioning
confidence: 99%
“…In an attempt to increase the rate of transplantation in blood group B candidates, the UNOS Board of Directors recently approved the use of a time-limited voluntary allocation variance enabling the transplantation of blood group A 2 and A 2 B cadaveric kidneys into blood group B recipients. Published reports have shown that blood group A 2 kidneys can be successfully transplanted into blood group B recipients, especially if they have low-titer anti-A antibodies (3). Performing this type of ABO incompatible transplant can increase the transplant rate of patients with blood group B (3).…”
Section: Do Minorities Have Decreased Access To Cadaveric Kidney Tranmentioning
confidence: 98%